Evaluation of Dental Implant Stability in Narrow Alveolar Ridges Utilizing Osseodensification Technique Versus Screw Expansion: A Randomized Single Blinded Clinical Trial - Nawfal Hasan Tofan; Ali H Abbas Hussaini (Wolters Kluwer Medknow Publications, 2024)
Introduction: We aimed to compare the implant stability quotient (ISQ) values of endosteal dental implants (DIs) inserted into narrow alveolar ridges via osseodensification (OD) versus manual screw expansion (SE). Methods: Nineteen patients were randomized into two groups. The patients ranged in age from 21 to 59 years, with 46 implant osteotomy sites and 41 DIs. Twenty DIs were installed using OD drilling (OD group), and 21 DIs were inserted using manual screw expander drills (SE group). Primary stability was measured at the surgery time, and secondary stability was measured at the 24th week using the Osstell ISQ device. A probability value < 0.05 was considered to be statistically significant. Results: No statistical difference was observed between the mean values of primary stability of the OD (ISQ: 67.06 ± 4.41) and SE (ISQ: 67.76 ± 4.79) groups (P = 0.518). No statistical difference was noted between the mean values of secondary implant stability of the OD (ISQ: 68.53 ± 6.70) and SE (68 ± 5.68) groups (P = 0.780). Conclusion: The OD technique is comparable with the manual SE counterpart in terms of primary and secondary stability.